Potential association between obstructive lung diseases and cognitive decline - Figat, Magdalena; Wiśniewska, Aleksandra; Plichta, Jacek; Miłkowska-Dymanowska, Joanna; Majewski, Sebastian; Karbownik, Michał S.; Kuna, Piotr; Panek, Michał G. (Frontiers in Immunology, 2024)
Introduction Chronic obstructive lung diseases, such as asthma and COPD, appear to have a more extensive impact on overall functioning than previously believed. The latest data from clinical trials suggests a potential link between cognitive deterioration and chronic obstructive inflammatory lung disease. This raises the question of whether these diseases affect cognitive functions and whether any relevant biomarker may be identified. Methods This prospective observational study included 78 patients divided equally into asthma, COPD, and control groups (n=26, 27 and 25 respectively). The participants underwent identical examinations at the beginning of the study and after at least 12 months. The test battery comprised 16 questionnaires (11 self-rated, 5 observer-rated, assessing cognition and mental state), spirometry, and blood samples taken for PKA and CREB mRNA evaluation. Results A 2.3-fold increase in CREB mRNA was observed between examinations (p=0.014) for all participants; no distinctions were observed between the asthma, COPD, and control groups. Pooled, adjusted data revealed a borderline interaction between diagnosis and CREB expression in predicting MMSE (p=0.055) in COPD, CREB expression is also associated with MMSE (β=0.273, p=0.034) like with the other conducted tests (β=0.327, p=0.024) from COPD patients. No correlations were generally found for PKA, although one significant negative correlation was found between the first and second time points in the COPD group (β=-0.4157, p=0.049),. Discussion Chronic obstructive lung diseases, such as asthma and COPD, may have some linkage to impairment of cognitive functions. However, the noted rise in CREB mRNA expression might suggest a potential avenue for assessing possible changes in cognition, especially in COPD; such findings may reveal additional transcription factors linked to cognitive decline.